2009
DOI: 10.1152/ajpcell.00626.2008
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 stimulates catabolism in C2C12 myotubes

Abstract: Interleukin-1 (IL-1) is an inflammatory cytokine that has been linked to muscle catabolism, a process regulated by muscle-specific E3 proteins of the ubiquitin-proteasome pathway. To address cellular mechanism, we tested the hypothesis that IL-1 induces myofibrillar protein loss by acting directly on muscle to increase expression of two critical E3 proteins, atrogin1/muscle atrophy F-box (MAFbx) and muscle RING-finger 1 (MuRF1). Experiments were conducted using mature C2C12 myotubes to eliminate systemic cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
137
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(149 citation statements)
references
References 77 publications
10
137
1
1
Order By: Relevance
“…Recent studies have shown that chronic exposure to IL-1β reduced myofibrillar proteins and myotube diameter in C2C12 culture (Li et al 2009), which is in apparent contrast to our observation indicating the promotion of myoblast growth and differentiation under IL-1β treatment. In potential explanation of this discrepancy the differences in experimental protocols should be taken into consideration, as Li et al (2009) used mature myotubes subjected to cytokine treatment, whereas in our study the effects of IL-1β on cell cycle regulatory mechanisms and the onset of myogenesis were investigated, and appeared to be limited in time to the period preceding myoblast fusion.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that chronic exposure to IL-1β reduced myofibrillar proteins and myotube diameter in C2C12 culture (Li et al 2009), which is in apparent contrast to our observation indicating the promotion of myoblast growth and differentiation under IL-1β treatment. In potential explanation of this discrepancy the differences in experimental protocols should be taken into consideration, as Li et al (2009) used mature myotubes subjected to cytokine treatment, whereas in our study the effects of IL-1β on cell cycle regulatory mechanisms and the onset of myogenesis were investigated, and appeared to be limited in time to the period preceding myoblast fusion.…”
Section: Discussioncontrasting
confidence: 99%
“…Both plasma IL-1β and hindlimb muscle ubiquitin-proteasome pathway were elevated in tumor-bearing and cachectic mice (Cannon et al 2008). According to in vivo (Cai et al 2004) and in vitro studies (Luo et al 2003, Chevrel et al 2005 IL-1β activated p38 MAPK and NF-kB: the signaling elements that promote the proteolysis in muscle and the reduction of myofibrillar proteins (Li et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the view that MuRF1 acts as an atrogin, its expression is intimately associated with muscle wasting in numerous clinical conditions (as reviewed in Bodine and Baehr2) or following exposure to pharmacological treatments (e.g. glucocorticoids, inflammatory cytokines, reactive oxygen species7, 8, 9, 10), while its gene inactivation confers partial resistance to muscle wasting conditions 7, 8, 11, 12. Therefore, several approaches have attempted to down‐regulate MuRF1 activity therapeutically, either directly in vitro via targeted inhibition of MuRF1 by a muscle‐specific small molecule13 and adenoviral knockdowns14, 15 or indirectly in vivo via exercise training16 or antioxidant administration17, which resulted in a significant reduction in muscle wasting.…”
Section: Introductionsupporting
confidence: 52%
“…This catabolic response to endotoxic/septic shock in skeletal muscle involves increased protein breakdown, but also reduced protein synthesis and inhibition of amino acid uptake. Numerous reports have documented the potential contribution of GC (32), proinflammatory cytokines (33,34), and LPS (35) to this effect. However, recent studies have substantially evidenced that GC were indeed requisite to this process, because activation of the genes involved in muscle atrophy after LPS-induced peripheral inflammation was essentially blocked by adrenalectomy (36).…”
Section: Discussionmentioning
confidence: 99%